Disproving the Presence of Paleozoic‐Triassic Metamorphic Rocks on the Island of Zannone (Central Italy): Implications for the Early Stages of the Tyrrhenian‐Apennines Tectonic Evolution. Issue 12 (2nd December 2020) - Curzi, Manuel; Billi, Andrea; Carminati, Eugenio; Rossetti, Federico; Albert, Richard; Aldega, Luca; Cardello, Giovanni Luca; Conti, Alessia; Gerdes, Axel; Smeraglia, Luca; Van der Lelij, Roelant; Vignaroli, Gianluca; et al.
Abstract: The inner Apennines (Italy) are characterized by scattered outcrops of continent‐derived orogenic metamorphic units exposed along the Tyrrhenian coast from northern to southern Apennines. At least since the 1970s, some peculiar rocks exposed on Zannone Island (central Italy) have been described as the only Paleozoic‐Triassic metamorphic complex linking those exposed in the northern—with those in the southern Apennines. Assessing the protolith nature, thermobaric conditions, and structural features of what is accepted to be the metamorphic unit of Zannone is, therefore, crucial to elucidate the early paleotectonic evolution of the Apennines‐Tyrrhenian orogenic system. To that end, we interpreted seismic reflection profiles offshore Zannone, we carried out mesoscale and microscale structural investigations of representative outcrops on the island, performed X‐ray diffraction analysis, and K‐Ar and U‐Pb geochronology of representative clay gouge and syntectonic carbonate veins. Results show that the metamorphic rocks of Zannone can actually be reinterpreted as belonging to nonmetamorphic siliciclastic turbidites, likely deposited in foredeep settings, and coeval to the Oligocene‐Miocene Macigno Fm. of the northern Apennines. The turbiditic sequence was overthrust by Triassic dolostone in the early Miocene ( 22 Ma), weakly deformed at <200°C, and downfaulted by postorogenic extensional faults starting 7 Ma ago. Hence, Zannone represents a unique geological location in central Italy where to study the innermost (i.e. oldest) thrust sheet of the central‐northern Apennines, thereby shedding new light onto the early tectonics of the Apennines. Based on this evidence, a new evolutionary scheme for the early stage of the Apennines tectonic evolution is proposed. Key Points: Discovery of a hitherto unknown early thrust in the Apennines New radiometric dating of Apennine tectonic phases Reinterpreting and overturning of a long‐held assumption in the Apennines